Endogenous Neural Stem Cell Mediated Oligodendrogenesis in the Adult Mammalian Brain - Daniel Z. Radecki; Jayshree Samanta (Cells, 2022)
Oligodendrogenesis is essential for replacing worn-out oligodendrocytes, promoting myelin plasticity, and for myelin repair following a demyelinating injury in the adult mammalian brain. Neural stem cells are an important source of oligodendrocytes in the adult brain; however, there are considerable differences in oligodendrogenesis from neural stem cells residing in different areas of the adult brain. Amongst the distinct niches containing neural stem cells, the subventricular zone lining the lateral ventricles and the subgranular zone in the dentate gyrus of the hippocampus are considered the principle areas of adult neurogenesis. In addition to these areas, radial glia-like cells, which are the precursors of neural stem cells, are found in the lining of the third ventricle, where they are called tanycytes, and in the cerebellum, where they are called Bergmann glia. In this review, we will describe the contribution and regulation of each of these niches in adult oligodendrogenesis.